The Use of Suffixes in Narrative Writing: A Case Study of Thai EFL Learners - Sama , Kamariyah; Huda, Tanzil; Rasuki, Muhlisin (National Multidisciplinary Sciences, 2023)
This study investigates the use of English suffixes in narrative writing by Thai learners of English as a foreign language. Given the significance of suffixes in second/foreign language acquisition, understanding how Thai learners employ suffixes in narrative contexts is crucial. A descriptive approach was adopted, with data collected from 12 eighth-grade students at Tarbiatulwatan Mulniti Junior High School in Thailand. The students' narrative writing assignments were analyzed to identify their usage of key inflectional suffixes (-ed, -s/es, -est, and -ing) and derivational suffixes (e.g., -ly). The findings revealed that students commonly utilized inflectional suffixes to mark past tense, plural nouns, and superlative adjectives. However, some students demonstrated difficulties with spelling, particularly when converting words ending in "y" to "i." Additionally, the use of derivational suffixes was limited, with only a few instances of employing the -ly suffix to form adverbs. These findings shed light on Thai learners' proficiency in using English suffixes in narrative writing and have implications for language pedagogy. Understanding the challenges they face can aid educators in developing targeted instructional strategies to enhance suffix usage. Further research is warranted to explore factors influencing the learning of derivational suffixes and to extend this study to learners of varying proficiency levels.